Respostas

2013-10-31T11:54:58-02:00
A) 3 - ( 3x - 6) = 2x + ( 4 - x)
     3 - 3x + 6 = 2x + 4 -x
      -3x -2x + x = 4 - 6 - 3
         -5x + x = 4 - 9
            - 4x = - 5              x(-1)
               4x = 5
                  x= 5/4

b)4 . ( x - 2 ) = 4 + 2 . ( x - 1)
    4x - 8 = 4 + 2x - 2
    4x - 2x = - 2+4 +8
       2x = 10
         x = 10/2
         x= 5

c) 7x - 3 . ( x - 2) = 3 . ( x + 4)
     7x -3x + 6 = 3x + 12
      7x - 3x - 3x = 12 - 6
       7x - 6x = 6
            x = 6
d) 2 . ( y -2) + 5 . ( 2 - y) = - 3 . ( 2y + 2)
    2y - 4 + 10 - 5y = - 6y - 6
    2y - 5y + 6y = - 6 - 10 + 4
    8y - 5y = -16 + 4
          3y = - 12
            y = -12/3
            y = - 4

e) 2 .(  1 - t ) + 1 = 3 . ( t -3) - 2t
     2 - 2t + 1 = 3t - 9 - 2t
      - 2t - 3t +2t = - 9 - 1 - 2
         -5t + 2t = - 12
           - 3t = -12           x( -1)
              3t = 12
               t = 12/3
               t = 4
f) 5 .( m + 1 ) - 3 . ( 2m + 1) = 4 . ( 5 -m)
    5m + 5 - 6m - 3 = 20 - 4m
     5m - 6m + 4m = 20 + 3 - 5
     9 m - 6m = 23 - 5
       3m = 18
        m= 18/3
        m = 6










2013-10-31T12:06:02-02:00

essas são as respostas das questões, estão um pouco simplificadas mais estão corretas.

 

a) 3-3x+6=2x+4-x

-4x=-5

x= 5/4

b) 4x - 8= 4 + 2x - 2

 x = 10

c) 7x - 3x + 6= 3x + 12

x= 6

d) 2y - 4 + 10 - 5y = 6y + 6

-9y = 0

y = 0

e) 2 - 2t + 1 = 3t - 9 - 2t

t = -12/-3

t=4

f) 5m + 5 - 6m - 3 = 20 - 4m

3m = 18

m = 6

Aqui escreva a resposta